Giant primary adrenal hydatid cyst presenting with arterial hypertension: a case report and review of the literature - Tazi, Fadl (BioMed Central, 2012)
INTRODUCTION: A primary hydatid cyst of the adrenal gland is still an exceptional localization. The adrenal gland is an uncommon site even in Morocco, where echinococcal disease is endemic. CASE PRESENTATION: We report the case of a 64-year-old Moroccan man who presented with the unusual symptom of arterial hypertension associated with left flank pain. Computed tomography showed a cystic mass of his left adrenal gland with daughter cysts filing the lesion (Type III). Despite his negative serology tests, the diagnosis of a hydatid cyst was confirmed on surgical examination. Our patient underwent surgical excision of his left adrenal gland with normalization of blood pressure. No recurrence has occurred after 36 months of follow-up. CONCLUSION: There are two remarkable characteristics of this case report; the first is the unusual location of the cyst, the second is the association of an adrenal hydatid cyst with arterial hypertension, which has rarely been reported in the literature.